Family Socioeconomic Status and Chinese Adolescents’ Academic Achievement in the Arts: The Mediating Role of Family Arts Resources and the Moderating Role of Family Arts Atmosphere - Yuan, Wen; Guo, Hui; Fung, C. Victor; Chen, Fumei; Liu, Lisha; Xu, Liangyuan; Li, Yanfang (Frontiers in Psychology, 2021)
In the present study, we examined the association between family socioeconomic status (SES) and adolescents’ academic achievement in the arts and the mediating and moderating roles of family process factors. Chinese adolescents (N = 8,723) in Grade 8 reported characteristics of family SES, family arts resources, and family arts atmosphere, and then completed a standardized test assessing academic achievement in music and visual art. The results showed that family SES significantly predicted adolescents’ level of academic achievement in the arts after controlling for adolescents’ gender and school location. The effect of family SES on adolescents’ academic achievement in the arts was partly mediated by family arts resources, constituting 20.51% of the total predicted effect. In addition, family arts atmosphere moderated the association between family SES and adolescents’ achievement in the arts. Specifically, family SES had a stronger relationship with academic achievement in the arts for adolescent with higher family arts atmosphere than for adolescent with poor family arts atmosphere. Findings in this study expands the field of influence of the family environments and enhance an understanding of the influence mechanisms of family environments on arts learning.